2022
DOI: 10.1039/d2cc00838f
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity vs. selectivity of quinone methides: synthesis of pharmaceutically important molecules, toxicity and biological applications

Abstract: Quinone methides (QMs) are considered to be highly reactive intermediates because of their aromatization both in chemical and biological systems. Being highly accessible, quinone methides (QMs) have been widely exploited...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…126−128 Despite the fact that these aberrant alkylation processes disrupt normal cellular metabolism and induce cytotoxicity, it has been shown that they can be harnessed for therapeutic purposes. 129,130 For instance, Wijtmans et al 131 demonstrated that the cytotoxicity of a derivative of aspirin (NO-ASA) is attributed to the generation of QMs in its metabolism rather than the production of nitric oxide or aspirin itself.…”
Section: Bioactive Sipsmentioning
confidence: 99%
See 1 more Smart Citation
“…126−128 Despite the fact that these aberrant alkylation processes disrupt normal cellular metabolism and induce cytotoxicity, it has been shown that they can be harnessed for therapeutic purposes. 129,130 For instance, Wijtmans et al 131 demonstrated that the cytotoxicity of a derivative of aspirin (NO-ASA) is attributed to the generation of QMs in its metabolism rather than the production of nitric oxide or aspirin itself.…”
Section: Bioactive Sipsmentioning
confidence: 99%
“…SIPs based on poly­(benzyl carbamate), poly­(benzyl carbonate), and poly­(benzyl ether) could generate a large amount of quinone methides (QMs) and their analogues upon degradation. These QMs are highly reactive electrophilic molecules capable of coupling with many important biomolecules such as nucleic acids, proteins, and glutathione via 1,6-nucleophilic addition reactions, leading to alkylation products. Despite the fact that these aberrant alkylation processes disrupt normal cellular metabolism and induce cytotoxicity, it has been shown that they can be harnessed for therapeutic purposes. , For instance, Wijtmans et al demonstrated that the cytotoxicity of a derivative of aspirin (NO-ASA) is attributed to the generation of QMs in its metabolism rather than the production of nitric oxide or aspirin itself.…”
Section: Sip-based Drug Delivery Systemmentioning
confidence: 99%
“…Quinone methides (QMs) have an exocyclic conjugate system with two opposite polarized groups, which allows them to be involved in 1,6-conjugate addition reactions. [1][2][3] In particular, the formation of a benzylic adduct by the addition of oxygen-, sulfur-, and nitrogen-centered nucleophiles at the exocyclic methylene-or methine-group sites is always accompanied by the in situ aromatization of the formal cyclohexadiene ring. [4][5][6] Consequently, QMs are reactive intermediates widely involved in the biosynthesis of natural products and applied in the organic synthesis of valuable compounds.…”
Section: Introductionmentioning
confidence: 99%
“…24 One possible limitation with some of these approaches is the generation of electrophilic byproducts such as a quinone methide 13,14,18,21,24 or an aldehyde; 11,16,17,20 such byproducts may contribute to electrophilic stress. 25,26 Also, there is a need for secondary assays to report persulfide produced by these donors. To overcome the need for secondary assays to report persulfide generation, a latent fluorophore strategy can be employed.…”
mentioning
confidence: 99%